PEREMPUAN AMERIKA DAN PERJUANGANNYA PASCA PERANG DUNIA II - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT This research discusses American women and their struggle in post of World War H. This is a library research which is based on sources about women struggle and dilemmas faced by women in social, economy, and politic roles. This research uses interdisciplinary approach in discipline of American studies. This thesis attempts to perceive, interpretation, and analysis of the American women and their struggle in the context of history, psychology, and politics in society. This research begins with the note of American women history as an introductory. Then it goes on to interpret and discuss the women struggle in American politics before and after World War II. In this research, the writer finds that American women struggle in social, economy, and politics increases, however the role of women in politics still a problem in American society. It is signed by the number of women who get position in American government since 1970s to 1990s only 25%. Therefore, there is a discrimination based on stereotype from American culture and society which regard women are not suitable involving in politics. This stereotype is an obstacle for women to involve in politics. Keywords: Struggle -- Politics -- World War II -- Stereotype